2001
DOI: 10.1179/135100001101536445
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in haemodialysis – intradialytic changes

Abstract: Oxidative stress is likely to be involved in the development of complications due to haemodialysis. Though there is evidence for production of oxygen free radicals during haemodialysis, reports on net oxidative imbalance due to a single dialysis session are conflicting. Hence, a time-course analysis of changes in lipid peroxides (LPO) along with antioxidant enzymes and vitamins was carried out. Hourly changes in LPO and antioxidants were studied during a first-use cuprophan membrane and acetate dialysis in 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The lowest levels were observed in children on maintenance HD. These results are consistent with the data obtained in adult patients with CRF [28, 29]. Moreover, Taccone-Gallucci et al [30] demonstrated the beneficial effect of vitamin E supplementation by decreasing MDA in erythrocytes of uremic patients.…”
Section: Discussionsupporting
confidence: 82%
“…The lowest levels were observed in children on maintenance HD. These results are consistent with the data obtained in adult patients with CRF [28, 29]. Moreover, Taccone-Gallucci et al [30] demonstrated the beneficial effect of vitamin E supplementation by decreasing MDA in erythrocytes of uremic patients.…”
Section: Discussionsupporting
confidence: 82%
“…However a signifi cant increase of the OS value was noted immediately after hemodialysis. These results are in accordance with other researchers [19][20][21][22] who reported that OS was exacerbated by the dialysis session. Other researchers reported having the opposite result.…”
Section: Discussionsupporting
confidence: 83%
“…Elevated NO levels in CRF patients, which significantly decreased after dialysis, and evidence for production of oxygen free radicals during HD have been reported. 25,26,27 The present study showed increased levels of FFAs, TG, TC and decreased HDL-C and Ph-lipids in predialysis samples as a consequence of carnitine deficiency with no significant changes after dialysis. After L-carnitine supplementation the FFAs, TC and HDL-C returned to control levels while TG and Ph-lipids continued to be significantly different from controls.…”
Section: Discussionmentioning
confidence: 84%